Предмет: Алгебра,
автор: elenaksd
Помогите решить производную
Приложения:
Ответы
Автор ответа:
0
y=(2x+1)/x(x+1)
y'=((2x+1)/x(x+1))'
используем формулу
u/v=(u'/v-yv')/v^2
y'=(2x+1)'(x^2+x)-(2x+1)(x^2+x)'/((x^2+x))^2
y'=2*(x^2+x)-(2x+1)(2x+1)/((x^2+x))^2
y'=2x^2+2x-4x^2-2x-2x-1/((x^2+x))^2
y'=(-2x^2-2x-1)/((x^2+x))^2
y'=((2x+1)/x(x+1))'
используем формулу
u/v=(u'/v-yv')/v^2
y'=(2x+1)'(x^2+x)-(2x+1)(x^2+x)'/((x^2+x))^2
y'=2*(x^2+x)-(2x+1)(2x+1)/((x^2+x))^2
y'=2x^2+2x-4x^2-2x-2x-1/((x^2+x))^2
y'=(-2x^2-2x-1)/((x^2+x))^2
Похожие вопросы
Предмет: Геометрия,
автор: aventarez1234
Предмет: Геометрия,
автор: Sasha11m11m1
Предмет: Қазақ тiлi,
автор: nrzha
Предмет: Литература,
автор: книгамира
Предмет: Алгебра,
автор: byms1